Find the solution of the equation 2x^3+e^x=0 using the 3 iterations of Newton's method.
-
Newton's method says that successively better approximations to
the solution of f(x) = 0 may be had using the following algorithm:
x(n+1) = x(n) - f [x(n)] / f '[x(n)]
It's always good to start as close as you can to where you think the solution is.
2x^3 + e^x = 0 OR
e^x = -2x^3
I look at that last equation as a means to make a reasonable estimate of where to start.
The left side is an exponential that is always positive and the right side is a decreasing cubic that crosses the x-axis at x = 0. The solution to the equation (if there be one) must be an x < 0.
Also notice in the original equation both the cubic and the exponential are increasing functions for all x and 2x^3 is zero at x = 0 so if you add another increasing function to it, the y value will reach zero BEFORE x = 0.
f(x) = 2x^3 + e^x
f '(x) = 6x^2 + e^x
and x - f(x) / f ' (x) = [4x^3 + e^x(x - 1)] / [6x^2 + e^x]
Storing g(x) = [4x^3 + e^x(x - 1)] / [6x^2 + e^x] into a calculator capable of that function and using an educated guess of x = -0.5:
First approximation is about -0.669250134
second approximation is about -0.64192804
third approximation is about -0.64100635
fourth approximation is about -0.64100533182
Fifth really hones-in at -0.641005331819
And the sixth is so close to the fifth that the digits the calculator gives are all the same to 12 decimals.
the solution of f(x) = 0 may be had using the following algorithm:
x(n+1) = x(n) - f [x(n)] / f '[x(n)]
It's always good to start as close as you can to where you think the solution is.
2x^3 + e^x = 0 OR
e^x = -2x^3
I look at that last equation as a means to make a reasonable estimate of where to start.
The left side is an exponential that is always positive and the right side is a decreasing cubic that crosses the x-axis at x = 0. The solution to the equation (if there be one) must be an x < 0.
Also notice in the original equation both the cubic and the exponential are increasing functions for all x and 2x^3 is zero at x = 0 so if you add another increasing function to it, the y value will reach zero BEFORE x = 0.
f(x) = 2x^3 + e^x
f '(x) = 6x^2 + e^x
and x - f(x) / f ' (x) = [4x^3 + e^x(x - 1)] / [6x^2 + e^x]
Storing g(x) = [4x^3 + e^x(x - 1)] / [6x^2 + e^x] into a calculator capable of that function and using an educated guess of x = -0.5:
First approximation is about -0.669250134
second approximation is about -0.64192804
third approximation is about -0.64100635
fourth approximation is about -0.64100533182
Fifth really hones-in at -0.641005331819
And the sixth is so close to the fifth that the digits the calculator gives are all the same to 12 decimals.
-
So first of all, it should be clear that this doesn't have a simple analytic solution. You can use Newton's method to get successively better approximations of x:
2x^3 = -e^x
x^3 = -1/2 e^x
x = cuberoot (-1/2 e^x)
Plug in x = 0 on the right, and you get:
x_1 = cuberoot (-1/2 e^0) = cuberoot (-1/2) ~= -.7937
x_2 = cuberoot (-1/2 e^(-.7937)) ~= -.6092
x_3 = cuberoot (-1/2 e^(-.6092)) ~= -.6478
You can keep going to get better and better approximations.
Note:
Some equations like this have a closed form in terms of something called the "Lambert W() Function." Lambert W is the function such that x = W(x) e^W(x). In this case:
2x^3 = e^x
cuberoot(2) x = e^(x/3)
cuberoot(2) x e^(-x/3) = 1
-x/3 e^(-x/3) = -1/(3cuberoot(2)) = -cuberoot(4) / 6
-x/3 = W(-cuberoot(4)/6)
x = -3 W(-cuberoot(4)/6)
You would not be expected to find this answer though, and this wasn't what the question asked.
2x^3 = -e^x
x^3 = -1/2 e^x
x = cuberoot (-1/2 e^x)
Plug in x = 0 on the right, and you get:
x_1 = cuberoot (-1/2 e^0) = cuberoot (-1/2) ~= -.7937
x_2 = cuberoot (-1/2 e^(-.7937)) ~= -.6092
x_3 = cuberoot (-1/2 e^(-.6092)) ~= -.6478
You can keep going to get better and better approximations.
Note:
Some equations like this have a closed form in terms of something called the "Lambert W() Function." Lambert W is the function such that x = W(x) e^W(x). In this case:
2x^3 = e^x
cuberoot(2) x = e^(x/3)
cuberoot(2) x e^(-x/3) = 1
-x/3 e^(-x/3) = -1/(3cuberoot(2)) = -cuberoot(4) / 6
-x/3 = W(-cuberoot(4)/6)
x = -3 W(-cuberoot(4)/6)
You would not be expected to find this answer though, and this wasn't what the question asked.
-
1+1=2